The theory of ‘de-schooling’ between paradox and utopianism - Nassif, Ricardo (1975)
The theory of 'de-schooling society' and of 'disestablishing school' is not -particularly as regards the latter aspect- entirely new, neither does it find its only expression s in the thinking of Ivan Illich and his co-author, Everett Reimer. Nevertheless they are -Illich in particular- held to be the most explicit and coherent exponents of the doctrine. As this is undoubtedly true, it is on them that my study will be focused.